Approach of pulmonologists in Turkey to noninvasive mechanical ventilation use in acute respiratory failure - OLGUN YILDIZELİ, ŞEHNAZ (TURKISH ASSOC TUBERCULOSIS & THORAX, 2015)
Introduction: Noninvasive mechanical ventilation (NIV) has been increasingly used worldwide for acute respiratory failure (ARF), especially in patients with chronic lung disorders. We aimed to define the approach of pulmonologists in Turkey to NIV use for ARF management. Materials and Methods: A 38-question survey, developed and tested by authors, was distributed by e-mail to a total of 2.205 pulmonologists in Turkey. Results: Response rate was 27% (n=596). Seventy-one percent of responders were practicing NIV in clinic. NIV use was found to be associated with responder's academic title, age, duration of medical license, type of physician's hospital and its region, patient load, NIV experience during residency, and duration of NIV and intensive care unit (ICU) experience (p<0.001). Based on sub-group analysis of responders using NIV, median number of NIV patients followed-up per week was 4 [interquartile range (IQR): 2-6]. Most of the NIV users reported employment of wards (90%) and/or ICUs (86%) to follow-up patients, while 8.4% of the responders were applying NIV only in ICU's. Chronic obstructive lung disease (COPD) (99.5%), obesity hypoventilation syndrome (93.7%) and restrictive lung disease (89.4%) were the most common indications. Majority of NIV users (87%) were applying NIV to > 60% of patients with COPD, and success rate in COPD was reported as over 60% by 93% of users. Oronasal mask (median and IQR 90, 80-100%, respectively) and home care NIV ventilators (median and IQR 50, 10-85%, respectively) were the most commonly utilized equipment. Conclusion: NIV use in ARF varies based on hospital type, region and, especially, experience of the physician. Although consistent with guidelines and general practice, NIV use can still be improved and increased.
Keywords: Noninvasive ventilation; acute respiratory failure; survey; chronic obstructive pulmonary disease; intensive care unit; general wards; POSITIVE-PRESSURE VENTILATION; STANDARD MEDICAL THERAPY; ACUTE-CARE HOSPITALS; WARD; MORTALITY; DISEASE; TRENDS; TRIAL; COPD